Social psychology: The standard version: Hewstone, M, Stroebe, W & Stephenson, G M (1996) Introduction to social psychology: A European perspective (2nd ed.). Oxford: Blackwell Publishers. 698 pages. ISBN 0631-18585-2. - Durrheim, Kevin (PINS-Psychology in Society, 2026)
The bookshelves of social psychology are brimming over with undergraduate texts. New publications are being churned out and old faithfuls updated at an impressive rate. Each seeks to outdo the other in becoming glossier, more user-friendly, and more relevant to “real life issues” than the next. The consumer may well feel spoiled for choice. Yet, on closer inspection one observes that, just like different brands of cola on the supermarket shelf, not much separates these texts: they all include the traditional topics such as attitudes, love and attraction and intergroup processes; they all discuss the same "classic" experiments; their empiricist style is the same; and they even include many of the same photographs. Nowadays, these text also come standard with "test banks" instructor manuals, and other ancillaries.